Analysis of Fine Dust Impacts on Incheon and Busan Port Areas Resulting from Port Emission Reduction Measures - Moon-Seok Kang; Jee-Ho Kim; Young Sunwoo; Ki-Ho Hong (Atmosphere)
PM2.5 concentrations in major port cities in the Republic of Korea, such as Incheon and Busan, are as serious as those in land-based metropolises, such as Seoul, and fine dust generated in port cities is mainly emitted from ships. To identify the specific substances influencing local air quality, the occurrence and effects of high concentrations of PM2.5 at the ports of Incheon and Busan were analyzed. To analyze the effects of improving air quality based on the Republic of Korea’s port and ship-related reduction measures, we calculated an emissions forecast for 2025 following the implementation/non-implementation of these measures and analyzed all impacts using the WRF-SMOKE-CMAQ modeling system. The ratio of ionic components constituting PM2.5 at the ports of Incheon and Busan was generally high in nitrate composition; however, the ratio of sulfate was high on high PM2.5 concentration days. When implementing measures to reduce emissions related to ports and ships, forecasted PM2.5 and SO2 emissions showed substantial decreases in port areas as well as nearby land and sea areas. The associated decrease in the PM2.5 concentration was highly influential in reducing the concentration of sulfate.